Pengaruh Kemampuan Dan Motivasi Terhadap Kinerja (Studi Pada Guru SMK Palapa Semarang) - Sekti, Arum Wibowo; Bodroastuti, Tri (Jurnal Kajian Akuntansi dan Bisnis, 2012)
In achieving good performance in a company, people have a verystrategic position for man know inputs that need to be taken out of the environment, howto get and capture these inputs using technology, able to manage and transform inputsinto outputs which meet the public. Performance is often defined as the achievement oftasks, of which the performance is necessary to indicate the degree of success or failureof organization in achieving the organizations vision, mission, and goals, so to know theresults that have been achieved in the framework of the process towards establishedgoals. To achieve this leadership role to improve and provide motivation is veryimportant. Therefore, this study aimed to analyze the influence of ability and motivationon teacher performance at SMK Palapa Semarang. The population in this study was theoverall 45 people are teachers, and the entire population was sampled. The analyticaltool used in this study was multiple linear regression. The results showed that based onhypothesis testing motivation and ability simultaneously had a significant effect on theteacherâs performance of SMK Palapa Semarang. The magnitude influence of ability andmotivation was 19.334 with a 3.219 or F table value F count = 19.334> F table 3.219.Partially, motivation was the most dominant factor affecting the teacherâs performance atSMK Palapa Semarang as motivation was enough to determine the tasks of the employeeso optimize the performance, it needs motivation of the employer.Keywords: Performance, Abilities and Motivation